The problem with the valuation of parks in historical manor-houses in rural areas in Poland - Rosłon-Szeryńska, Edyta; Łukaszkiewicz, Jan; Fortuna-Antoszkiewicz, Beata (Economics and Environment, 2019)
Manor-house parks are an important part of natural and cultural landscape of Polish countryside. While sites designated as historical do enjoy an elevated “social” status, this does not always translate into its monetary market value. Own research shows large price discrepancies in property appraisal reports for the same real estate. The discrepancies were related to valuation of vegetation (Rosłon-Szeryńska, 2018). Even though there are many methods and techniques of appraisal (including: profit-, market-, cost-oriented or mixed) available in specific legal acts and standards, apprising vegetation is still problematic. The goal of this research is to evaluate reasons behind these glaring discrepancies in appraisal of manor-house and park complexes in rural communes. Research included an analysis of current market prices of 100 historical real estates comprised of a manor-house and apark from all over the country. Regression analysis proves that the share of park’s value in the overall historical real estate price is too low. This particularly applies to parks with an area of less than 5 ha.